THE SUBSURFACE RESISTIVITY STUDIES IN GAMPONG JAWA WASTE DISPOSAL BANDA ACEH - Fadhli Syamsuddin; Marwan Abu Bakar; Nur Mala (Jurnal Natural, 2012)
The research has been carried out about determining the subsurface resistivity values by using the VLF method in waste disposal (TPA) Gampong Jawa Banda Aceh. Measurement target is for investigate allegations of contaminant substances are disposed by the public at these locations based on the response of the magnetic and electric fields. The tools used are the T-VLF device with two electrodes and using three stations, namely the transmitter JJF4 Japan, NWC Australia and UMS Moscow. Broad expanse of measurements on L1 and L2 is 200 m, L3 and L4 is 150 m. There are 74 measuring points with spacing of 10 m. The result of this experiment showed that the four layers can be divided into two layers with different resistivity values. The first layer at a depth of 0-15 m with apparent resistivity of 2-25 Ωm, allegedly at this layer contained the contaminant substances. The second layer at a depth of 15 m with apparent resistivity of 25-101 Ωm, in this layer are water-resistant coating that can withstand water into and out of the landfill.